2015
DOI: 10.1021/am508213c
|View full text |Cite
|
Sign up to set email alerts
|

Concerted Mitigation of O···H and C(π)···H Interactions Prospects Sixfold Gain in Optical Nonlinearity of Ionic Stilbazolium Derivatives

Abstract: DAST (4-dimethylamino-N-methyl-4-stilbazolium tosylate) is the most commercially successful organic nonlinear optical (NLO) material for frequency-doubling, integrated optics, and THz wave applications. Its success is predicated on its high optical nonlinearity with concurrent sufficient thermal stability. Many chemical derivatives of DAST have therefore been developed to optimize their properties; yet, to date, none have surpassed the overall superiority of DAST for NLO photonic applications. This is perhaps … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
45
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(47 citation statements)
references
References 36 publications
2
45
0
Order By: Relevance
“…In organic π‐conjugated materials, selective control of intermolecular interactions in the solid state is a very crucial issue to obtain the desired physical properties correlated to electronic and vibrational states . In particular, alterations in the intermolecular interactions of organic nonlinear optical materials can result in dramatic changes in the molecular ordering of chromophores, macroscopic nonlinear optical responses, and molecular vibrational and phonon modes, which are important material characteristics in diverse nonlinear optical and THz photonic applications…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In organic π‐conjugated materials, selective control of intermolecular interactions in the solid state is a very crucial issue to obtain the desired physical properties correlated to electronic and vibrational states . In particular, alterations in the intermolecular interactions of organic nonlinear optical materials can result in dramatic changes in the molecular ordering of chromophores, macroscopic nonlinear optical responses, and molecular vibrational and phonon modes, which are important material characteristics in diverse nonlinear optical and THz photonic applications…”
Section: Introductionmentioning
confidence: 99%
“…In well‐known and commercially available pyridinium‐based crystals, the first‐order hyperpolarizability of chromophores in the crystalline state (β crystal ) is considerably less than in solution (β solution ); e.g., in stilbazolium and merocyanine crystals, β crystal is only about 20% and 5%, respectively, of the corresponding β solution . In a more precise analysis of intermolecular interactions of stilbazolium‐based crystals, reducing intermolecular interactions (edge‐to‐face π–π interactions and hydrogen bonds (H··· − O‐S) between cationic chromophores and aromatic anions) shows the possibility to enhance the macroscopic nonlinear optical activity in the crystalline state by more than a factor of six in DAST (4‐(4‐( N,N ‐dimethylamino)styryl)‐1‐methylpyridinium 4‐methylbenzenesulfonate) crystals . Therefore, the development of new molecular engineering approaches that simultaneously achieve 1) control of specific intermolecular interactions of chromophores and 2) perfectly parallel chromophore alignment in the solid state is extremely important for nonlinear optical materials.…”
Section: Introductionmentioning
confidence: 99%
“…So far several attempts have been undertaken and reported to find correlations between the absorption spectra and NLO response for NLO active materials [40][41][42]. Coradin et al [42] demonstrated that the active for the second harmonic generation (SHG) materials obtained by intercalation of cationic chromophore 4-[4-(dimethylamino)-R-styryl]-1-methylpyridinium iodide (DAMS+I-) into the layered MPS 3 (M=Cd, Mn) matrices revealed the strong narrow band around 580 nm in the solid state UV-vis absorption spectra, assigned to the aggregation of chromophores in the J-type aggregates [38].…”
Section: Spectroscopic Studiesmentioning
confidence: 99%
“…In the crystalline form, the different levels of electronic states (e.g., HOMO and LUMO), along with their gaps and broadening, are related to absorption and fluorescence characteristics and they are sensitive to many factors including the intermolecular interaction parameters in the crystal structure [13,20e22,42,43]. For example, the electronic states of p-conjugated materials in the crystalline form can be influenced by Coulombic interactions and intermolecular hydrogen bonds [13,20].…”
Section: Physical Propertiesmentioning
confidence: 99%
“…4), the dipole moment m and the electronic levels of the HMQ cations in the crystalline state are also affected differently [13,20].…”
Section: Physical Propertiesmentioning
confidence: 99%